Unsur-Unsur Teknologi Dalam Novel Sementara, Selamanya. Karya Ika Natassa - Fillah Syakur Azindha; Eva Dwi Kurniawan (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The novel Sementara, Selamanya by Ika Natassa is a literary work that tells the story of the relationship between two husband and wife characters during the Covid-19 pandemic in 2020 which occurred in the city of Jakarta. Not only does it tell an interesting relationship between husband and wife, but this novel also provides a different perspective on the role of technology in helping to establish harmony between husband and wife, which requires them to be separated due to the ongoing pandemic. This paper aims to analyze the role of technology used in novel stories. The method used in this paper uses a hermeneutical approach. The results of research analysis using a hermeneutic approach provide a deeper interpretation of the technology in the novel. By using this approach, the research results provide a more in-depth picture of technology as well as the development of relationships and changes in traits between characters during the Covid-19 pandemic.